2023
DOI: 10.5483/bmbrep.2023-0070
|View full text |Cite
|
Sign up to set email alerts
|

AcrAB-TolC, a major efflux pump in Gram negative bacteria: toward understanding its operation mechanism

Abstract: Antibiotic resistance (AR) is a silent pandemic that kills millions worldwide. Although the development of new therapeutic agents against antibiotic resistance is in urgent demand, this has presented a great challenge, especially for Gram-negative bacteria that have inherent drug-resistance mediated by impermeable outer membranes and multidrug efflux pumps that actively extrude various drugs from the bacteria. For the last two decades, multidrug efflux pumps, including AcrAB−TolC, the most clinically important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…Efflux pumps are important membrane proteins that play a crucial role as defense mechanisms by actively exporting harmful substances, such as antibiotics, detergents, and heavy metals ( Jang, 2023 ). In our study, all of the isolates studied harbored acrA , encoding a subunit that functions as an adapter protein linked to AcrB, and TolC outer membrane channel proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Efflux pumps are important membrane proteins that play a crucial role as defense mechanisms by actively exporting harmful substances, such as antibiotics, detergents, and heavy metals ( Jang, 2023 ). In our study, all of the isolates studied harbored acrA , encoding a subunit that functions as an adapter protein linked to AcrB, and TolC outer membrane channel proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The periplasmic lipoprotein, AcrA, is classified as a fusion protein that bridges the outer and inner membranes [ 35 ]. The AcrB is a membrane protein located in the cytoplasmic membrane, and the TolC is an outer membrane protein [ 36 , 37 ]. Together they form AcrAB-TolC tripartite efflux pump system ( Figure 3 A).…”
Section: Discussionmentioning
confidence: 99%
“…PAβN is a synthetic efflux pump inhibitor that counteracts the activity of RND family efflux pumps [ 40 ]. The modified dipeptide-amide inhibits antibiotic efflux through the AcrAB-TolC system [ 37 ]. A computational simulation showed that PAβN binds to AcrB and inhibits efflux pumps at several residues [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The active efflux pump in gram-negative bacteria consists of three components: an outer membrane protein, a membrane fusion protein, and an efflux protein or transporter on the inner membrane. The RND efflux pump AcrAB-TolC, which is composed of a periplasmic fusion protein AcrA, a plasma membrane transporter AcrB, and an outer membrane channel protein TolC, plays an important role in the process of multidrug resistance in E. coli [53]. Before the drug acts on the intracellular target site, it binds to the plasma membrane transporter AcrB and is expelled from the cell through AcrA and the outer membrane channel TolC.…”
Section: Reduction In Antibiotic Intracellular Accumulationmentioning
confidence: 99%